Output Gap Estimates in the WAEMU Zone - Thioune, Thierno (International Journal of Economics and Financial Issues, 2019)
The concepts of potential output and output gap are important tools for central banks and in particular CBWAS to forecast inflation in pursuit of its priority objective of controlling inflation. In this sense, the choice of a method for their estimation is tricky. This work proposes an estimation of the potential production by the unobservable component methods and proposes a comparison with the production function widely used in the literature and recognized as the best method of estimating the potential production for the WAEMU countries. Two methods with unobservable components are taken into account in this work. This is the approach of Watson (1986) and that of Kuttner (1994). The results indicate that the different approaches as well as the production function explain the various periods of crisis identified within the Union. However, the comparative analysis reveals that only the output gap estimated by the approaches of Watson (1986) and Kuttner (1994) have significant and positive effects on inflation while the output gap obtained by the production function does not explain inflation. Keywords: Output gap, Inflation,WAEMU JEL Classifications: E23, E32, E31, C51, O55 DOI: https://doi.org/10.32479/ijefi.8076